Antibacterial Activity Test Of Ethanol Extract And N-Hexane Fraction, Ethyl Acetate, Moringa Leaf Water (Moringa Oleifera L) Against Streptococcus Mutans ATCC 25175 Bacteria - Wahdah Sri Rahayu; Tatiana Siska Wardani; Tiara Ajeng Listyani (CV. AFDIFAL MAJU BERKAH, 2026)
Dental caries remains a major oral health problem globally and in Indonesia, triggered by Streptococcus mutans biofilm. Chemical agents such as chlorhexidine have side effects, encouraging the use of natural alternatives from Moringa oleifera L. leaves. This study aims to evaluate the antibacterial activity of ethanol extracts and n-hexane, ethyl acetate, and water fractions against Streptococcus mutans ATCC 25175, identify the most active fraction, and determine the MIC and MBC. This quantitative study used diffusion and dilution methods. Bacteria: Streptococcus mutans ATCC 25175; samples: ethanol extract of Moringa oleifera L. leaves and n-Hexane, ethyl acetate, and water fractions. Data analysis used SPSS 25 One-Way ANOVA, Tukey (p<0.05). Results showed that the ethyl acetate fraction was the most active with 12.36 mm inhibition at 45%; MIC and MBC were 30% ANOVA significant (p=0.000). The ethyl acetate fraction has strong caries prevention potential, supporting herbal development.